The Effect of High Switching Frequency on Inverter Against Measurements of kWh-Meter - Isdawimah, Isdawimah; Setiabudy, Rudy; Gunawan, Ridwan (Institut Teknologi Sepuluh Nopember, 2014)
In PV systems connected to the grid requires a kWh meter to measure the amount of power delivered to the grid, and an inverter to convert the DC voltage generated by PV into AC voltage. The latest generation of Inverter using the high switching frequency to obtain the inverter with good efficiency, small in sizes and lightweight. This led to the emergence of harmonics to the grid through the instrument of kWh meter, and caused the kWh-meter is not working properly. This study is intended to obtain the minimum value of the switching frequency which affect the results of measurement of Digital kWh meters. Kwh-meter tested by varying the switching frequency which is obtained from various types of inverters and from the simulator of switching of high frequencies.